The Individual and Combined Effects of Fusaric Acid and T-2 Toxin in Broilers and Turkeys - Ogunbo, S.O.; Broomhead, J.N.; Ledoux, D.R.; Bermudez, A.J.; Rottinghaus, G.E. (International Journal of Poultry Science, 2007)
Two experiments were conducted to evaluate the individual and combined effects of fusaric acid (FA) and T-2 toxin (T-2) in broiler chicks and turkey poults. In each experiment, 80 day-old birds were allotted randomly to a 2×2 factorial arrangement with treatments of 0 and 250 mg FA/kg feed and 0 and 4 mg T-2/kg feed. Diets were fed to 4 pen replicates of 5 birds each for 21 days. Feed intake and body weight gain of poults were reduced (p<.05) by the T-2 and the FA-2 combination diets. Poults fed T-2 and the FA-2 combination diets were also less efficient (p<.05) in converting feed to gain. There were no treatment effects (p>.05) on performance of broilers. Poults fed FA and the FA-2 combination diets had increased (p<.05) heart weights, whereas chicks fed FA and the FA-2 combination diets had increased (p<.05) kidney weights. Poults fed the combination FA-2 diet had higher (p<.05) serum AST values compared to all other treatments. Poults fed the T-2 and FA-2 combination diets had increased (p<0.05) serum Na but reduced (p<0.05) serum Mg. Uric acid concentrations were higher (p<0.05) in chicks fed the FA and FA-2 combination diets. Oral lesions were present in chicks (68%) and poults (100%) fed T-2 with or without FA. Data indicate no toxic synergy when FA and T-2 were fed simultaneously to broilers and turkeys at these dietary concentrations.